PENGARUH CELEBRITY ENDORSER DAN TESTIMONIAL PRODUK TERHADAP KEPUTUSAN PEMBELIAN MASKER ORGANIK MUDDY BUDDY SECARA ONLINE - Pratiwi, Friska Dian; Andayani, Sri; Maruta, IGN Anom (Jurnal Dinamika Administrasi Bisnis, 2020)
Promotion is the most important thing for business owners. Promotional methods that are currently popular is using celebrity endorsers and product testimonials. This research entitled "Influence Celebrity Endorsers and Product Testimonials on the Purchasing Decision by Online of Organic Mask Muddy Buddy at @muddybuddykedirisby have a problem statement is there any influence of celebrity endorsers and product testimonials on purchasing decisions orgabic mask Muddy Buddy by online at @muddybuddykedirisby. The purpose of this research is how much influence of celebrity endorsers and product testimonials on purchasing decisions orgabic mask Muddy Buddy by online at @muddybuddykedirisby. Type of this research is field research. The method used is quantitative analysis and data collection techniques using questionnaire. The data used are primary data obtained from subjects, Muddy Buddy mask consumers at @muddybuddykedirisby, and secondary data obtained by reading literature, books, journals, data from the internet and previous thesis. based on data analysis, partially and simultaneously Celebrity Endorsers and product testimonials have a positive and significant effect towards the purchase decision organic Mask Muddy Buddy by Online at @muddybuddykedirisby. In this research,s expected online shop @muddybuddykedirisby can choose the right celebrity endorser and then trying to get product testimonials with pict or photos and posting in @muddybuddykedirisby’s social media continuously to increase purchases.Keywords: Celebrity Endorser, Product Testimonials, Buying Decision.